Kontribusi Industri Halal dalam Pertumbuhan Produk Domestik Bruto di Indonesia - Ilman Miftahul Fauzi; Muhammad Gesta Nugraha Fauzi; Mochamad Syahril Sabar Suryana; Lina Marlina (SIL'AH: Jurnal Ekonomi Syariah, 2025)
The existence of the halal industry is often notseen as having a significant influence on Indonesia's gross domestic productgrowth. However, the halal industry itself not only emphasizes thehalal aspect of products, but also considers ethical and sustainable production processes. This study aims to identify the contribution ofthe halal industry to gross domestic product growth in Indonesia.This study uses a descriptive approach and secondary data analysis, where the data we obtained came from previous studies and reliable data centers. Based on the data and analysis we have conducted, this study shows that the halal industry has a strategic role in strengthening the national economic structure, increasing exports, and creating jobs. These findings confirm that the development of the halal industry can be used as one of the main drivers of Indonesia's economic growth in the future.